Hyaline vascular-type Castleman's disease of the retroperitoneum - Wei-Feng Huang; Yi Ding; Wei Liu (Archives of Clinical Gastroenterology - Peertechz Publications, 2022)
A 39-year-old man with newly diagnosed and well controlled hypertension was in his usual state of good health. He was diagnosed with a retroperitoneal tumor during a health check-up, which was suspicious of adrenal tumor by abdominal computed tomography.